FLAVONOIDS FROM ENDOPHYTIC BACTERIA OF COSMOS CAUDATUS KUNTH. LEAF AS ANTICANCER AND ANTIMICROBIAL - RAMADHAN, FIQIH; Mukarramah, Luluk; OKTAVIA, FIKRI AINUR RISMA HARDIYANTI; Yulian, Ria; Annisyah, Nurul Hilyatun; Asyiah, Iis Nur (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The present study aimed to isolate and examine the characteristics of endophytic bacteria from kenikir (Cosmos caudatus Kunth.) leaves, to determine the endophytic bacteria capable of producing flavonoids, and to test their potency as anticancer and antimicrobial. Methods: The isolation of endophytic bacteria from C. caudatus Kunth. leaf was conducted by technical surface sterilization. Each of these isolates was produced from the insulation and then cultured on a liquid medium of 0.1% soluble starch, 0.5% peptone, and 0.15% yeast extract with a pH of 7 which have been incubated in room temperature for 5 days with agitation of 120 rpm and extracted with ethyl acetate solvent. The extract was then tested for flavonoid content using thin-layer chromatography method. The anticancer ability of flavonoids was tested by brine shrimp lethality test (BSLT) method, while that for antimicrobial, the test used paper disc method. Results: A total of 15 isolates of endophytic bacteria were successfully isolated from the kenikir leaves, but only 4 isolates produced flavonoids, among others PKM 1 (Serratia sp.), PKM 2 (Neisseria sp.), PKM 17 (Acinetobacter sp.), and PKM 19 (Yersinia sp.). BSLT test results showed that the flavonoids cause mortality in Artemia salina leach with LC50 as much as 16.736 in PKM 17, 17.267 in PKM 2, 18.672 in PKM 1, and 23.411 in PKM 19. The flavonoids also inhibited the growth of pathogens in human-based antimicrobial test results. Conclusion: Flavonoids produced by four endophytic bacterial isolates from kenikir leaves have great potential as anticancer and antimicrobial.